Dampak Agriculture on Agreement (AoA) terhadap Perdagangan Hortikultura Indonesia - Jamhari; Agus Dwi Nugroho (Journal of World Trade Studies, 2012)
The Indonesian trade in horticulture indicates that the value of imports is higher than the value of exports for raw or processed commodities. The purpose of this study is to analyze the performance of import, the competitiveness and the factors that affect Indonesia's import of garlic, onions, potatoes and oranges. Type of data used in this study is secondary data from the years of 1991-2010. The analysis of competitiveness is based on Revealed Comparative Advantage (RCA) and Acceleration Ratio (AR). Error Correction Model (ECM) is utilized to investigate the factors affecting the import of Indonesian horticultural. The trend in Indonesian garlic, onions, potatoes and oranges import has showed an increase. However, Indonesia has a low competitiveness and acceleration export of garlic, onions, potatoes and oranges. The results also shows that the availability of garlic per capita affects the import of garlic. Agreement on Agriculture (AoA) policies significantly affect the import of garlic and onion. While the ratio of the price of domestic products with international product prices affect the import of all commodities.